SAKARATUL MAUT DALAM PERSPEKTIF Al-QUR’AN MENURUT NASKAH SYEIKH ZAINAL ABIDIN BIN MUHAMMAD ALFATONI - Rapiqi, Apzalul; Hanisah, Pipit; Zilpa, Indah; Kalsum, Umi (JURNAL DIALOKA: Jurnal Ilmiah Mahasiswa Dakwah dan Komunikasi Islam, 2023)
Abstract: Every living thing must die. Death must be understood as something that must happen so that humans can live well and face death with good preparation. The purpose of this research is to understand the meaning of sakaratul maut according to the book of Syeikh Abidin. This research is a library study. The results show that (a) death is a condition in which the spirit begins to separate from the body, (b) the virtue of remembering death is that it can increase human fear of Allah SWT. So that they can continue to prepare for death, (c) the sense of Sakaratul is divided into three stages of disaster, the testimony of the angel of death, which can cause feelings of horror and fear in the heart for a year, like those who commit immorality, who witness hell, and where they are very afraid. the dark places are full of worms, and the conditions that people receive are according to their deeds in the world. Abstrak: Setiap yang hidup hidup pasti mati. Kematian harus dipahami sebagai sesuatu yang pasti terjadi agar manusia dapat hidup dengan baik dan menghadapi kematian dengan persiapan yang matang. Tujuan dari penelitian ini adalah untuk memahami pengertian sakaratul maut menurut dalam kitab Syeikh Abidin. Penelitian ini merupakan studi kepustakaan.. Hasil penelitian menunjukkan bahwa (a) kematian adalah keadaan dimana ruh mulai terpisah dari jasad, (b) keutamaan mengingat kematian adalah dapat meningkatkan rasa takut manusia kepada Allah SWT. Agar mereka dapat terus mempersiapkan kematian, (c) rasa Sakaratul dibagi menjadi tiga tahap bencana, yaitu rasa sakit yang begitu mengerikan ketika nyawa dicabut, kesaksian malaikat maut, dan kondisi yang diterima manusia sesuai dengan perbuatan mereka di dunia.